Penerapan Teori Harapan Victor Vroom dalam Meningkatkan Motivasi Kerja Karyawan - Dahrani, Dahrani; Sohiron, Sohiron (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Motivation is a complex process that influences an individual's strength, direction and persistence in achieving goals. This article explores the application of Victor Vroom's Expectancy Theory to increase employee work motivation in various sectors. Vroom's theory emphasizes the importance of individual beliefs about the relationship between effort, performance, and results in driving motivation. Using content analysis techniques, this research identifies themes and patterns from literature related to work motivation. The application of Vroom's motivation principles in the context of the public sector, education, and business shows that understanding expectations and desired outcomes can improve individual motivation and performance. For example, the implementation of financial incentives such as Performance Allowances (TPP) in the Wajo Regency Government and project-based learning models in education have shown positive results in increasing motivation. In addition, good governance practices that emphasize transparency and accountability are also in line with Vroom's principles. Organizations that align motivation strategies with employee expectations can achieve increased engagement, reduce dissatisfaction, and create a culture of continuous improvement. In conclusion, understanding and applying Vroom's Expectancy Theory can help organizations create a work environment that supports and significantly improves individual performance